Retrograded starch/pectin coated gellan gum-microparticles for oral administration of insulin: A technological platform for protection against enzymatic degradation and improvement of intestinal permeability - Meneguin, Andréia B. [UNESP] (2018)
Gellan gum microparticles coated with colon-specific films based on retrograded starch and pectin was developed for enhancing the oral release of insulin (INS). The system developed promoted an impressive protection of INS (80%) after 120 min of incubation with trypsin and alpha-chymotrypsin, while only 3% of free INS remained intact after the same time, possibility due to the calcium chelating activity of the polymers in inhibiting the proteolytic activity. In vitro INS release in media simulating the gastrointestinal portions revealed a pH-dependent behavior, as well as the significance of the coating in lowering the release rates in relation to their counterparts. The permeability of INS on Caco-2 cells monolayers and excised rat intestine were significantly improved, mainly due to the influence of the anionic polymers on tight junctions opening, along with the excellent mucoadhesive properties of the gellan gum. All these features together contributed greatly to the hypoglycemic effect observed after the oral administration of the INS-loaded MP in diabetic rats, with reduction of up to 51% of blood glucose levels. The important findings of this work should contribute to the advances about the search of alternatives for oral administration of INS.